Air Embolism after Central Venous Catheter Removal: Fibrin Sheath as the Portal of Persistent Air Entry - Meggiolaro Marco; Erik Roman-Pognuz; Baritussio Anna; Scatto Alessio (Case Reports in Critical Care)
Central venous catheterization is of common practice in intensive care units; despite representing an essential device in various clinical circumstances, it represents a source of complications, sometimes even fatal, related to its management. We report the removal of a central venous catheter (CVC) that had been wrongly positioned through left internal jugular vein. The vein presented complete thrombosis at vascular ultrasonography. An echocardiogram performed 24 hours after CVC removal showed the presence, apparently unjustified, of microbubbles in right chambers of the heart. A neck-thorax CT scan showed the presence of air bubbles within the left internal jugular vein, left innominate vein, and left subclavian vein. A vascular ultrasonography, focused on venous catheter insertion site, disclosed the presence of a vein-to-dermis fistula, as portal of air entry. Only after air occlusive dressing, we documented echographic disappearance of air bubbles within the right cardiac cavity. This report emphasizes possible air entry even many hours after CVC removal, making it mandatory to perform 24–72-hour air occlusive dressing or, when inadequate, to perform a purse string.